PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KERJA PT. LIXIL ALUMINIUM INDONESIA - Maha Putra; Qurrotun Nada Fauzi (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
PT. LIXIL Aluminum Indonesia is a manufacturing company engaged in the aluminum sash building sector. This study aims to find out how to increase employee productivity, also to find out how the influence of motivation, discipline and job satisfaction has an impact on employee productivity at PT. LIXIL Aluminum Indonesia. The sampling technique used non-probability sampling method with purposive sampling technique. While data collection techniques include observation, interviews and distribution of questionnaires. Then the data analysis technique used is multiple linear regression analysis. From the results of the research that has been done, it shows that work motivation, work discipline, and job satisfaction have a positive and significant effect on employee productivity at PT. LIXIL Aluminum Indonesia is proven from the t-count results and the significance value of each variable is more than the specified value. And simultaneously (together) all variables (work motivation, work discipline, and job satisfaction) based on the results of the coefficient of determination (R2) above it is found that work motivation, work discipline and job satisfaction can affect the work productivity of employees of PT. LIXIL Aluminum Indonesia is 79.6% of which the other 20.4% is influenced by other variables outside the variables in this study, such as work environment factors, access to companies and so on.